2004
DOI: 10.1113/jphysiol.2004.068171
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of human airway ciliary beat frequency by intracellular pH

Abstract: pH i affects a number of cellular functions, but the influence of pH i on mammalian ciliary beat frequency (CBF) is not known. CBF and pH i of single human tracheobronchial epithelial cells in submerged culture were measured simultaneously using video microscopy (for CBF) and epifluorescence microscopy with the pH-sensitive dye BCECF. Baseline CBF and pH i values in bicarbonate-free medium were 7.2 ± 0.2 Hz and 7.49 ± 0.02, respectively (n = 63). Alkalization by ammonium pre-pulse to pH i 7.78 ± 0.02 resulted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
67
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 69 publications
(70 citation statements)
references
References 76 publications
(121 reference statements)
3
67
0
Order By: Relevance
“…For ciliary beating measurement, ensuring that the tissues are handled and treated in a similar manner is critical, for example if medium change is implemented, it should be applied for all samples. Sutto and colleagues reported that pH affected the mammalian ciliary beating frequency 24 . Thus, when comparing beating frequencies between cells treated with different compunds/mixtures, pH adjustment should be considered to minimize the variability of ciliary beating measurement.…”
Section: Discussionmentioning
confidence: 99%
“…For ciliary beating measurement, ensuring that the tissues are handled and treated in a similar manner is critical, for example if medium change is implemented, it should be applied for all samples. Sutto and colleagues reported that pH affected the mammalian ciliary beating frequency 24 . Thus, when comparing beating frequencies between cells treated with different compunds/mixtures, pH adjustment should be considered to minimize the variability of ciliary beating measurement.…”
Section: Discussionmentioning
confidence: 99%
“…An increase in intracellular pH produces an increase in CBF, whereas a decrease in pH produces a decrease in CBF. 35 However, it is not known whether this effect is caused by modulation of kinase activity, even though an acidic pH has been shown to inhibit PKA function, 46 or the direct activation of ODAs of the axoneme. 47 Temperature has also been shown in many investigations to influence CBF, most likely through protein kinase C modulation., 36,37,48 Lower temperature tends to slow CBF.…”
Section: Dynamic Regulationmentioning
confidence: 99%
“…Ciliary activity accelerates in response to a variety of mechanical, [27][28][29] chemical, 30,31 hormonal, [32][33][34] pH, 35 and thermal stimuli (Table 1). 36,37 Extracellular nucleotides (adenosine and uridine) are especially potent regulators of epithelial functions stimulating mucociliary clearance through mucus secretion, increasing CBF, and gating ion channels involved in the maintenance of epithelial surface liquid volume.…”
Section: Dynamic Regulationmentioning
confidence: 99%
“…ALI cultures were placed in a customized chamber allowing independent perfusion of the basolateral and apical compartment, and mounted at room temperature onto the stage of the Nikon Eclipse microscope. If required, airway epithelial cells were permeabilized as described before (Sutto et al, 2004).…”
Section: Production Of Pseudo-typed Lentivirus Vectors and Infection mentioning
confidence: 99%